2021
DOI: 10.3390/jcm10235470
|View full text |Cite
|
Sign up to set email alerts
|

New Time-Related Insights into an Old Laboratory Parameter: Early CRP Discovered by IBM Watson Trauma Pathway Explorer© as a Predictor for Sepsis in Polytrauma Patients

Abstract: The University Hospital Zurich together with IBM® invented an outcome prediction tool based on the IBM Watson technology, the Watson Trauma Pathway Explorer®. This tool is an artificial intelligence to predict three outcome scenarios in polytrauma patients: the Systemic Inflammatory Response Syndrome (SIRS) and sepsis within 21 days as well as death within 72 h. The knowledge of a patient’s future under standardized trauma treatment might be of utmost importance. Here, new time-related insights on the C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…This study has shown similar results, with PCT values reaching their maximum after 24 hours. A previous study with the same polytrauma patient cohort at the University Hospital Zurich has shown that CRP is predictive for sepsis even earlier than PCT, 6-8 hours after admission to the hospital [32] However, in many studies, CRP had no ability for sepsis in trauma patients [8][9][10][11][12]28,30,[33][34][35]. Further investigations have to be conducted to compare the predictive values of PCT with other biomarkers such as IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown similar results, with PCT values reaching their maximum after 24 hours. A previous study with the same polytrauma patient cohort at the University Hospital Zurich has shown that CRP is predictive for sepsis even earlier than PCT, 6-8 hours after admission to the hospital [32] However, in many studies, CRP had no ability for sepsis in trauma patients [8][9][10][11][12]28,30,[33][34][35]. Further investigations have to be conducted to compare the predictive values of PCT with other biomarkers such as IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…3653 patients were included for analysis in Watson Trauma Pathway Explorer, based on an ongoing database (2022) introduced on 01.08.1996. In both groups, lactate values were measured at formerly [5] defined time points (admission, 1, 2, 3, 4, 6, 8, 12, 24, and 48 h and 3, 4, 5, 7, 10, 14, and 21 days) after admission to the trauma bay of the University Hospital Zurich.…”
Section: Patient Collective Samplementioning
confidence: 99%
“…Accurate triaging plays a pivotal role in patient admission to the trauma bay. For such, various measured and calculated parameters are taken into account to estimate the risk of adverse events (AE) and mortality [1][2][3][4][5]. Recently, the University Hospital of Zurich and IBM collaborated for the construction of an artificial intelligence tool to predict the outcome [Systemic Inflammatory Respiratory Syndrome (SIRS) and sepsis within 21 days, and death within 72h] in polytrauma patients, based on a data sample of more than 3500 patients with ongoing admission [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this need, this study group collaborated with IBM to develop the IBM WATSON Trauma Pathway Explorer©, a visual analytics tool that predicts outcomes in severely injured individuals [ 4 , 5 , 6 , 7 , 8 ]. This validated and interactive tool utilizes clinical and laboratory values to predict various outcomes, including the occurrence of sepsis after a patient’s admission.…”
Section: Introductionmentioning
confidence: 99%